Investing in Public Health Microbiology Laboratories in Western Balkan Countries Enhances Health Security From Communicable Disease Threats in Europe - Bajoriniene, Agne; Leitmeyer, Katrin C.; Struelens, Marc J.; Kokki, Maarit H., Observers; Alternate Observers to the ECDC National Microbiology Focal Points in Western Balkan Countries; ćirković, Ivana; Boshevska, Golubinka; Dedeić-Ljubović, Amela; Koraqi, Andi; Kurti, Arsim; Mulliqi-Osmani, Gjyle; et al. (Frontiers in Public Health, 2019)
The European Centre for Disease Prevention and Control (ECDC), under the EU enlargement policy, has supported national efforts of Western Balkan countries to strengthen their communicable disease prevention and control systems. The new EU strategy “A credible enlargement perspective for and enhanced EU engagement with the Western Balkans” advocates transformation processes that will build the foundation of EU-oriented national reforms. Well-functioning public health microbiology laboratories are key for early detection and control of infectious diseases, and thus maintaining and enhancing health security in Europe. In order to help Western Balkan countries to improve their national capacities, ECDC facilitated needs assessments and identified key areas for advancement towards effective public health microbiology systems. Countries identified gaps in their laboratory data reporting and exchange systems. Harmonized and effective procedures for handling of highly contagious agents and cross-border transportation of biological samples were often lacking, as well as the systematic use of diagnostic testing at the primary care level or referral of patients, in particular for detection of antimicrobial resistance. There is a clear need to address the financial investment required for sustaining sufficient numbers of skilled laboratory workforce, laboratory supplies, and the development of new methods and techniques, including investment in emerging laboratory technologies, such as molecular typing by whole genome sequencing. This article highlights the key areas for investing in public health microbiology laboratories in Western Balkan countries needed to strengthen health security in Europe.